Transhumanisme Sebagai Sebuah Eskatologi Profetis (Sebuah Tinjauan Teologi Publik Tentang Transhumanisme) - Takalapeta, Teguh Lamentur (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2025)
Transhumanism is a movement that seeks to enhance human capacity through technology to create superhumans or posthumans who can live longer, be more intelligent, and be more prosperous. Neuralink developed by Elon Musk is one form of transhumanism that raises two ethical-theological issues related to human nature and eternal life. This paper attempts to wrestle with the relationship between theology and transhumanism related to these two issues by answering the main question: To what extent can theological sources be relevant to transhumanism? With a public theology approach, this paper presents various theological views on transhumanism. Finally, by putting forward several important notes, this study finds that prophetic eschatology is the most relevant theological source to open a deep dialogue between theology and transhumanism.